Reconstructing mothers' responsibility and guilt: Journalistic coverage of the 'Remedia Affair' in Israel. Issue 4 (August 2019) - Aronis, Carolin
This article explores journalistic representations of mothers during the horrific 'Remedia Affair', a 2003 tragedy in which dozens of Jewish Israeli babies fell sick and five died after being fed defective infant formula. The affair, a significant event in Israel's collective memory, was narrativized as a 'media scandal' with multiple discourses of guilt, blame and victimhood. Analysis of the linguistic and visual coverage of Jewish Israeli mothers in six newspapers shows how mothers were reconstructed as guilty for the loss of the babies' lives and well-being. In addition, the mothers were called to 'come back' to breastfeeding, an act that could have saved their children. Overall, this coverage reaffirmed the traditional social norms of the 'ideal Jewish mother' who sacrifices herself for her baby and is objectified as 'food', norms that were not commonly practiced by most Jewish Israeli families at the time.